PANoptosis in autoimmune diseases interplay between apoptosis, necrosis, and pyroptosis - Liu, Kangnan; Wang, Mi; Li, Dongdong; Duc Duong, Nguyen Truong; Liu, Yawei; Ma, Junfu; Xin, Kai; Zhou, Zipeng (Frontiers in Immunology, 2024)
PANoptosis is a newly identified inflammatory programmed cell death (PCD) that involves the interplay of apoptosis, necrosis, and pyroptosis. However, its overall biological effects cannot be attributed to any one type of PCD alone.PANoptosis is regulated by a signaling cascade triggered by the recognition of pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs) by various sensors.This triggers the assembly of the PANoptosome, which integrates key components from other PCD pathways via adapters and ultimately activates downstream execution molecules, resulting in cell death with necrotic, apoptotic, and pyroptotic features.Autoimmune diseases are characterized by reduced immune tolerance to self-antigens, leading to abnormal immune responses, often accompanied by systemic chronic inflammation. Consequently, PANoptosis, as a unique innate immune-inflammatory PCD pathway, has significant pathophysiological relevance to inflammation and autoimmunity.However, most previous research on PANoptosis has focused on tumors and infectious diseases, leaving its activation and role in autoimmune diseases unclear. This review briefly outlines the characteristics of PANoptosis and summarizes several newly identified PANoptosome complexes, their activation mechanisms, and key components. We also explored the dual role of PANoptosis in diseases and potential therapeutic approaches targeting PANoptosis. Additionally, we review the existing evidence for PANoptosis in several autoimmune diseases and explore the potential regulatory mechanisms involved.